ChemInform Abstract: An Oxidative Cyclopropanation Reaction of Primary Nitro Compounds Using Fe2O3. Issue 45 (October 2016) - Moriyama, Takaaki; Ito, Yuji; Koyama, Yusuke; Kawamoto, Takuji; Kamimura, Akio
Abstract: Alkenylnitro compounds (I) undergo oxidative cyclopropanation by treatment with Fe2 O3 in the presence of DBU and iodine.